HIGH SCHOOL STUDENTS’ PERCEPTION ON THE USE OF GOOGLE TRANSLATE FOR READING COMPREHENSION - Hasanah, Annisa; Delfi, Syofia; Daud, Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aimed to investigate students of SMAN 12 Pekanbaruperception of Google Translate use for reading comprehension. Random samplingtechnique was applied to decide the sample. There were 81 students as the participants.The instrument used was a questionnaire categorized into 5 components of perceptionsuch as students’ purposes of using GT, the use of GT, accuracy of GT, benefits of usingGT and drawbacks of using GT for reading comprehension. The findings indicated thatsenior high school students of SMAN 12 Pekanbaru have a positive perception onGoogle Translate use for reading comprehension. It showed that students put positiveperception of the purposes, use, benefits, and accuracy of Google Translate. Whilestudents have negative perceptions of the drawbacks of using Google Translate. Hence,the students are suggested to not fully rely on Google Translate and find another sourceto develop their proficiency in reading comprehension alongside Google Translate.Key Words: Perception, Google Translate, Reading Comprehension